Assessment of Water Quality Information System through Measurement Framework of ISO 15504 - Tri Sandhika Jaya (Jurnal Ilmiah ESAI, 2015)
Quality oriented and standardized process has begun to be implemented in some organizations. The standard expected is the one easily understood by any user organization and accepted by the organization globally. The standard is expected to minimize unproductive work. The purpose of this study was to measure the quality of water quality information system through the measurement framework of ISO 15504. The measurement framework uses the principles of Software Process Improvement and Capability Determination (SPICE). The results of measurements of the quality of the information system of water quality appear in levels which are classified into three levels, starting from level 1 to level 3. The results of the study showed that the water quality information system is still at level of 1, because it is only up to the implementation accomplished process. Key words: quality, information systems , ISO 15504 , SPICE